Faktor-Faktor yang Mempengaruhi Kriminalitas di Indonesia Tahun 2011-2016 dengan Regresi Data Panel - Kosmaryati Kosmaryati; Chandra Arinda Handayani; Refinanda Nur Isfahani; Edy Widodo (Universitas Sebelas Maret, 2019)
Criminality in Indonesia is increasing every year, therefore an effort is needed to reduce criminality in Indonesia, one of which can be used by knowing which factors influence the increase of criminality. This paper discusses the factors that influence criminality by using panel data regression analysis. Unemployment, domestic violence cases, narcotics cases, embezzlement cases, and fraud cases have positive effect on the amount of criminality with R2 of 0,85823 or 85,823%.Keywords : panel regression analysis, crime, Indonesia